Amnesia Narratives: Memory, Forgetting, and Identity - Jason Tougaw (European Journal of American Studies)
Amnesia fictions may be the most abundant precursors to the contemporary neuronovel. A cluster of recent, high-profile fiction and nonfiction amnesia narratives join a rapidly evolving tradition of neuronovels and brain memoirs, drawing on neuroscience to explore philosophical and social questions about the brain, identity, social relations, and history. While these texts vary in the representation of memory, forgetting, and identity, they share some fundamental elements: 1) They portray extreme instances of amnesia in order to explore philosophical and psychology questions about the role of forgetting in memory itself, 2) They offer detailed exploration of elements of identity that remain when memory is lost, and 3) They build worlds around their amnesiac characters, worlds designed to afford them respect, agency, and opportunities to express aspects of their identities that survive their failing memories.